COMPARATIVE TYPOLOGY OF GERMAN - UZBEKIAN LANGUAGES (BASED ON THE WOLF OF THE DESERT BY HERMANN HESSE) - Sattorova Marhabo Rahmonqulovna (American Journals, 2023)
The phenomenon of homonymy, which is described by the perfect or partial matching of linguistic units in the language, is one of the characteristics shared by the Uzbek and German languages. The primary unit of a language's vocabulary and the focus of lexicology study is the word. current linguistics word descriptions. the primary word symbols in contemporary German. The definition of the word according to conventional logic and linguistics. The word's lexical meaning and its several forms. The semantic structure of the word. Polysemy as a typical phenomenon in modern German. In this article, the comparative typology of German-Uzbek mants based on Hermann Hesse's desert wolf is discussed.
Keywords: German language, Uzbek language, typology, texts, comparative typology, semantic typology, linguistic typology, similar words, Hermann Hesse, the work